Comment: "Dynamics of Corporate Debt Management, Decision Rules, and Some Empirical Evidence" - Thakkar, Rashmi B. (Journal of Financial and Quantitative Analysis, 1974)
Rashmi B. Thakkar, Comment: "Dynamics of Corporate Debt Management, Decision Rules, and Some Empirical Evidence", The Journal of Financial and Quantitative Analysis, Vol. 9, No. 6 (Dec., 1974), pp. 1065-1066